Pivotal or peripheral: assessing the role of generative artificial intelligence in accelerating entrepreneurial success - a study of enhancing software engineering - Bakakis, Andreas (2023)
This thesis explores how Generative Artificial Intelligence (GAI) accelerates early-stage startups focusing on software engineering capabilities. By integrating literature review and expert interviews, it identifies GAI's role in mitigating failure factors and enhancing success factors. Findings suggest that GAI's impact varies across tasks, offering strategic advantages for startup development. The study provides actionable recommendations for founders to leverage GAI, guiding them through the challenges of entrepreneurship in the AI age. This research fills a significant gap, offering insights and directions for future inquiry into GAIenhanced startup ecosystems.